2002
DOI: 10.1152/ajpheart.00218.2002
|View full text |Cite
|
Sign up to set email alerts
|

α1-Adrenoceptor stimulation directly induces growth of vascular wall in vivo

Abstract: Previous studies suggesting that norepinephrine is directly trophic for the vascular wall have been confounded by concomitant hemodynamic disturbances. Herein, a microcatheter connected to an osmotic minipump was implanted adjacent to the rat carotid for 2-wk perivascular suffusion of agents at systemic levels ϳ1,000 times below the threshold for altering arterial pressure. Norepinephrine decreased lumen and adventitial areas and circumference by 10, 14, and 5%, respectively (all P Ͻ 0.05); a nonsubtype-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
97
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(111 citation statements)
references
References 32 publications
12
97
1
1
Order By: Relevance
“…60 Accelerated atherosclerosis, vasoconstriction, and proliferation of smooth muscle cells and adventitial fibroblasts in the vessel wall are further consequences of sympathetic activation related to progression of renal damage. 61,62 Norepinephrine exerts trophic effects on cardiac myocytes, and recent investigations demonstrated that cardiac sympathetic activity is related to left ventricular hypertrophy in patients with essential hypertension. 63 Sympathetic activation and vagal withdrawal are closely linked to cardiac arrhythmias, 64 which, in concert with the aforementioned factors, is partly responsible for the high rate of sudden cardiac death in patients with CRF.…”
Section: Adverse Consequences Of Sympathetic Activationmentioning
confidence: 99%
“…60 Accelerated atherosclerosis, vasoconstriction, and proliferation of smooth muscle cells and adventitial fibroblasts in the vessel wall are further consequences of sympathetic activation related to progression of renal damage. 61,62 Norepinephrine exerts trophic effects on cardiac myocytes, and recent investigations demonstrated that cardiac sympathetic activity is related to left ventricular hypertrophy in patients with essential hypertension. 63 Sympathetic activation and vagal withdrawal are closely linked to cardiac arrhythmias, 64 which, in concert with the aforementioned factors, is partly responsible for the high rate of sudden cardiac death in patients with CRF.…”
Section: Adverse Consequences Of Sympathetic Activationmentioning
confidence: 99%
“…Previous reports identified that treatments with norepinephrine (NE) could induce cardiac remodeling in rats (9,10), and increased sympathetic stimulation of the arteries might contribute to the arterial remodeling, which would be induced by α 1 -adrenoceptor-dependent proliferation, hypertrophy, and migration of vascular smooth muscle cells (VSMCs) and adventitial fibroblasts (11,12). These findings suggest that NE may contribute to adverse structural remodeling in hypertension.…”
Section: Introductionmentioning
confidence: 97%
“…They show that eutrophic (collagen deposition and fibrosis) and hypertrophic (proliferation and migration of smooth muscle cells and of adventitial fibroblasts) remodelling characterizes the damages caused by catecholamines on the vascular wall (1,(4)(5)(6)(7)(8)(9). These observations have also been indirectly confirmed by using a-adrenoceptor antagonists (9)(10)(11)(12)(13) and by experiments in animals submitted to local or systemic sympathetic denervation (14).…”
Section: Discussionmentioning
confidence: 82%
“…This direct trophic effect of catecholamines, mediated by a-adrenoceptors, concerns an increase in extracellular matrix, with consequent wall fibrosis and eutrophic remodelling. Moreover, in animal models employing balloon injury of the carotid or aorta, an exacerbation of this action may be observed with proliferation, hypertrophy and migration of smooth muscle cells and adventitial fibroblasts, leading to hypertrophic remodelling (1,(4)(5)(6)(7)(8)(9). The direct influence of sympathetic neurotransmitters on vascular wall structure has been supported by studies using a-adrenoceptor antagonists that showed a reduction in proliferation of vascular wall cells and in neointimal growth after vascular injury (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 97%